Estimation of Adsorption Parameters from Temperature-Programmed Desorption Thermograms: Application to the Adsorption of Carbon Dioxide onto Alumina - José A. Delgado; José L. Sotelo; José M. Gómez; Pilar Gómez (Adsorption Science & Technology, 2007)
In this work, a model is proposed for estimating the desorption activation energy from a TPD thermogram. The model considers the effects of diffusional resistance, the reactor cell volume, the sample weight and the carrier gas flow rate. The adsorption and desorption rate constants are estimated using theoretical expressions deduced from statistical thermodynamics, assuming first-order desorption kinetics. This model has been applied to the CO 2 /activated alumina system. The TPD thermogram has been obtained with a commercial apparatus, and the distribution of the desorption activation energy has been analyzed. A sensitivity analysis has been performed to determine the importance of different phenomena which can alter the position of the TPD peaks (re-adsorption, diffusional resistance, volume of sample cell). An experimental study of the effect of diffusional resistance has also been performed, comparing the TPD thermograms obtained with powdered and pelletized alumina. The experimental results have been compared with the model predictions.